Guardianship and custody of divorced couple’s children: welfare of the children or best interest of the child, a comparison study between Malaysia and Indonesia / Alizah Ali ... [et al.] - Ali, Alizah; M., QaharAwaka; Ismail, Noraini; Jangga, Rohani; Abu Bakar, Siti ZarikhSofia (UiTM Cawangan Johor, 2019)
There are several unavoidable matters that must be looked into when divorces happened. Properties and children are matters usually contested by divorced couples. Who should take care of the children and where are they going to be brought up are the subjective issues and depends on the circumstances of the individual case. The welfare concept of the child and best interest of the child are the clues that the family court must deal with delicately. The objective of this paper is to determine the application of these concepts by Malaysian law as compared to Indonesian law. This conceptual research paper will significantly indicate as to what extend these two countries successfully apply the theories of child welfare as well as best interest theories. The information gathered from books, articles, magazines and previous researches supported by the statutory and decided case are discussed thoroughly in accordance to recent situations. The Malaysian statutory solution refers to Law Reform Act (Marriage and Divorce) Act 1976 (Act 164), Guardianship of Infant Act 1961 (Act 351) while Indonesian statutory reference are Law No. 23 of 2002 on Child Protection jo. Law No. 35 of 2014 Amending Law on Child Protection and Law No. 1 of 1974 on Marriage. In addition, United Nations Convention on the Rights of the Child (UNCRC) are also discussed in this paper.